Viet Nam's water paradox [videorecording] /produced by the Information Office, Asian Development Bank ; director/videographer, Steven Griffiths ; script, Ian Gill, Steven Griffiths. - Griffiths, Steven; Gill, Ian (Asian Development Bank, 1996)
Each year, typhoons bring devastating floods to Viet Nam's countryside, exacting a heavy toll on human lives and crops. In contrast, Viet Nam's cities suffer from a chronic thirst for water due to an antiquated and dilapidated distribution system. This video shows how development projects aim to resolve this water paradox.